A multilateral system for plant genetic resources: Imperatives, achievements and challenges - Cooper, D.; Engels, J.; Frison, Emile A.; International Plant Genetic Resources Institute (1994)
Better use of plant genetic resources is critical to meeting the challenges of increasing food production and of alleviating poverty. All countries depend on plant genetic resources originating beyond their borders, which means that international cooperation is essential to secure continued access to these resources. International agreements are also necessary to guarantee their conservation. Both aims can be achieved only if there is an effective mechanism for sharing benefits with the countries that maintain these resources. This paper concludes that a multilateral system, within the framework of the Convention on Biological Diversity, is required to guarantee these objectives.